2019
DOI: 10.1001/jamaophthalmol.2019.1927
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Eye Care Use Among US Adults Aged 50 to 80 Years

Abstract: IMPORTANCE Contemporary data on use of eye care by US adults are critical, as the prevalence of age-related eye disease and vision impairment are projected to increase in the coming decades.OBJECTIVES To provide nationally representative estimates on self-reported use of eye care by adults aged 50 to 80 years, and to describe the reasons that adults do and do not seek eye care. DESIGN, SETTING, AND PARTICIPANTSThe National Poll on Healthy Aging, a cross-sectional, nationally representative online survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Those who had visits with an eye doctor may be more socioeconomically advantaged than those who did not. Ehrlich et al [ 29 ] found that unmarried, older adults with a low income were less likely than their more advantaged peers to report a recent eye examination, and common reasons for not having an eye examination included cost and lack of insurance coverage. Thus, the relationship between health care provider contact and internet use may reflect the digital divide because of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had visits with an eye doctor may be more socioeconomically advantaged than those who did not. Ehrlich et al [ 29 ] found that unmarried, older adults with a low income were less likely than their more advantaged peers to report a recent eye examination, and common reasons for not having an eye examination included cost and lack of insurance coverage. Thus, the relationship between health care provider contact and internet use may reflect the digital divide because of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of eye exams in our sample of diabetic African-American individuals aged 55 years and older was mirrored the findings of the National Poll on Healthy Aging. Among 2013 diabetic individuals aged 50 to 80 years, 72.2% reported undergoing an eye examination in the past year and 91.3% in the past two years [47]. According to the National Health and Nutrition Examination Survey over a 10-year period, vision impairment related to diabetes increased by 20% in the US population [48].…”
Section: Discussionmentioning
confidence: 99%
“…As the eye undergoes degenerative changes, disorders of lens disorders and glaucoma start to inflict the population [9]. Disorder of lens soared to the second most frequent category in the sixth decade of life and remained significant afterwards.…”
Section: Dominance Of Disorders Of Conjunctiva and The Variation Of Fmentioning
confidence: 99%